Embarking on an Action Plan: Proposing Vark Test as the Need Analysis for Classroom Teaching and Learning - Norhamizah Tamat; Noorulziwaty Kamaruzaman; Ezatul Marini Mohd Ghazali (Jurnal Pendidikan Indonesia, 2023)
Learning styles represent the different ways in which individuals prefer to learn and engage with educational content. Learning styles are based on the idea that people have unique cognitive strengths and preferences that can influence their learning experiences and outcomes. By understanding their learning styles, educators can tailor their instruction to meet students' individual needs. This personalized approach helps engage students more effectively and enhances their learning experience. Students are more likely to be engaged and motivated when taught in a manner that aligns with their preferred learning styles. This leads to increased participation, active involvement in the learning process, and improved retention of information. The objective of this research is to propose a VARK questionnaire as the basis for the need analysis in planning the action plan in the action research. This research employed the action research design using the Kemmis and Taggart model, is a widely recognized framework for conducting action research. The respondents selected for this research were 30 students of the Diploma in Quantity Survey of Politeknik Sultan Azlan Shah. The respondents consist of 15 female students and 15 male students. it was found that respondents have different learning styles according to their preferences which are categorized according to VARK learning styles.